Giovanni da Empoli (1483-1518): a florentine merchant in Portuguese Asia and the earliest specimens of birds of paradise in Europe (Passeriformes, Paradisaeidae) - Teixeira, Dante Martins (Arquivos de Zoologia, 2021)
According to the current literature, birds of paradise (Passeriformes, Paradisaeidae) arrived in Europe for the first time on 6 September 1522, when the single remaining ship of Fernão de Magalhães' fleet anchored in San Lúcar de Barrameda. It would therefore appear that the report by Florentine merchant Giovanni da Empoli concerning the presence of one these birds in Lisbon on 22 August 1514 – eight years earlier – has been entirely overlooked. Described by Empoli in a letter written in his own hand, composed in the Portuguese capital on 19 October 1514, this bird of paradise was acquired in Malacca and sent as a gift to Giovanni di Lorenzo de' Medici, who had assumed the pontifical throne on 9 March 1513 as Leo X. The same document mentions that King Manuel also possessed a bird of paradise, pointing to the possibility that these birds participated in the commerce of exotic animals and their products conducted by the Portuguese not long after the voyage of Vasco da Gama. In any case, this discovery allows an unexpected revision of the history of birds of paradise in Europe and could promote a search of new textual and iconographic sources.